THE RELATIONSHIP BETWEEN METABOLIC DISORDERS AND TUMOR PROGRESSION: REVIEW OF PRESENT DATA AND NEW THERAPEUTIC TARGETS - E. V. Semina; N. V. Danilova; N. A. Oleinikova; M. A. Agapov; K. A. Rubina (Сибирский онкологический журнал, 2021)
Background. Type 2 diabetes mellitus, obstructive sleep apnea, osteoarthritis and certain types of cancer are known to correlate with obesity. The mechanisms underlying the link between metabolic disorders and cancer remain obscure, yet assuming a potentially important role of reduced insulin sensitivity, altered glucose metabolism in tumor cells (the so-called Warburg effect), changes in the spectrum of secreted adipokines or interaction with their cognitive receptors as well as changes in steroid sex hormone production.Material and methods. A search for articles published in peer-reviewed journals indexed in pubmed, Wos, scopus and Rsci was carried out. More than 150 articles devoted to the study of the relationship between metabolic disorders and tumor progression were analyzed, of which 69 were included in this review.Results. The main strategy of anticancer therapy is to suppress the proliferation of tumor cells and metastasis. However, one should take into consideration a significant role of additional factors that can enhance side effects of anticancer therapy, ensure the resistance of tumor cells to chemotherapy or change cancer cell metabolic profile. New data recently emerging in the literature indicate an important function of proteins such as t-cadherin and urokinase receptor (upar) and their possible involvement in the regulation of tumor cell metabolism, in particular, sensitivity to insulin and adipose tissue hormones. The review encompasses recent data on the involvement of t-cadherin and upar in the regulation of metabolism and proposes a model explaining the relationship between these proteins and metabolic disorders associated with the processes of carcinogenesis and chemoresistance of cancer cells.Conclusion. Understanding of the factors and mechanisms that support obesity and metabolic disorders is relevant both for the development of cancer preventive measures and optimization of therapeutic strategies for combating cancer.